2023
DOI: 10.3390/ijms24098397
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Structural and Thermodynamic Properties of Starch during Potato Tuber Dormancy

Abstract: The main reserve polysaccharide of plants—starch—is undoubtedly important for humans. One of the main sources of starch is the potato tuber, which is able to preserve starch for a long time during the so-called dormancy period. However, accumulated data show that this dormancy is only relative, which raises the question of the possibility of some kind of starch restructuring during dormancy periods. Here, the effect of long-term periods of tuber rest (at 2–4 °C) on main parameters of starches of potato tubers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The downregulated gene set was enriched with starch metabolism, photomorphogenesis, and Circadian Rhythm-Plant pathways. Previous research has substantiated the pivotal role of starch metabolism in regulating potato sprouting [15], illustrating that the concurrent suppression of isoamylases ISA1, ISA2, and ISA3 can accelerate sprouting [16], whereas inhibiting α-amylase StAmy23 tends to delay sprouting [17]. Photomorphogenesis and Circadian Rhythm-Plant pathways play a crucial role in regulating plant development.…”
Section: Transcriptome Unveils Potential Mechanisms Of Hs Affecting P...mentioning
confidence: 98%
“…The downregulated gene set was enriched with starch metabolism, photomorphogenesis, and Circadian Rhythm-Plant pathways. Previous research has substantiated the pivotal role of starch metabolism in regulating potato sprouting [15], illustrating that the concurrent suppression of isoamylases ISA1, ISA2, and ISA3 can accelerate sprouting [16], whereas inhibiting α-amylase StAmy23 tends to delay sprouting [17]. Photomorphogenesis and Circadian Rhythm-Plant pathways play a crucial role in regulating plant development.…”
Section: Transcriptome Unveils Potential Mechanisms Of Hs Affecting P...mentioning
confidence: 98%
“…Throughout the dormancy period, the starch in potato tubers remains metabolically and structurally unstable, suggesting that tubers undergo ongoing biochemical and physical changes despite their dormant state. Studies have shown that the average size of starch grains in stored potato tubers increases, with a concomitant decline in the frequency of smaller grains [53]. This observation suggests that starch granules, especially the smaller ones, may undergo a fusion process during tuber dormancy.…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Thus, dormancy appears to be associated with an increase in structural defects within the starch matrix. The storage stage not only alters the starch's crystalline structure but also leads to the proliferation of these defects [53]. Notably, the melting of starch at lower temperatures suggests the dissolution of more defective crystalline lamellae relative to those that melt at elevated temperatures.…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%